Characterisation of recycled aluminium swarf into fine powder for MIM applications via ball milling / Sarah Balqis Yussoff ... [et al.] - Yussoff, Sarah Balqis; Mohd Nor, Nor Hafiez; Husain, Hazran (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Abstract. Practically, aluminium swarf (chips) collected from an automotive production line is less likely to have any contaminants once the lubricants are removed. In theory, metals do not degrade in value and can be used infinitely. Nowadays, industrial waste management is one of the factors of an enormous concern as the environment is showing prominent signs of ruin, decay, pollution and exhaustion. Thus, recycling or reusing metals in a much energy efficient means aligns with helping to save the environment from rapid collapsion by paddling backwards in excessive energy and resource exhaustion. In powder metallurgy, a branch of manufacturing known as metal injection moulding (MIM) utilises powdered metals to produce high quality parts with zero waste productions. Hence, this study aims produce usable fine powders (50 μm >) from aluminium metal swarf using ball mills which is suitable for MIM applications. Overall, the smallest powder particle size (< 45 μm) of the pulverised aluminium swarf collected shows that 90% are smaller than 61.645 μm in diameter and 50% are smaller than 34.829 μm in diameter after 2 (two) operating cycles of ball milling. The particle shape came out to be irregular but far smoother and bulkier than of a previously flaky texture. Besides that, the purity of the pulverised aluminium swarf is exceptionally comparable to a commercially pure aluminium powder at 91.4wt%. The remaining weight percentage belongs to traces of silicone (Si) that may have been present during swarf (chip) formation from abrasive cutters during production or from cleaning media of the ball mill apparatus. It is found that the key to fine aluminium powder production via ball mill is the size of the grinding media; the smaller the diameter, the smaller the powder particle size produced. Equally important is the milling time, which is kept at 3 minutes and 27 minutes of pause time for adequate jar and grinding media cooling; which reduces the tendency of particle agglomerations.